Employment elasticity of output growth in Kazakhstan economy: Recent evidence from a macroeconomic perspective - Bhat, Javaid Ahmad; Imtiyaz ul Haq; Bhat, Sajad Ahmad; Megits , Nikolay (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
This study aims to understand the dynamics of aggregate and sectorial employment elasticity of output growth in the Kazakhstan economy from 1996 to 2019. To serve our purpose, a rolling regression method with a window of 6 years has been used to estimate aggregate and sectoral employment elasticity, and an ARDL bounds testing approach has been incorporated to assess the impact of various macroeconomics determinants. The results indicate the existence of a cointegration relationship, and the employment elasticity of output growth in Kazakhstan’s economy has declined at aggregate and sectoral levels, thus indicating jobless growth. More specifically, the results reveal that inflation, trade openness and the exchange rate are negatively associated with employment elasticity. In contrast, a positive association is established between service sector employment share, the population growth rate and employment elasticity of output growth. The study recommends strengthening macroeconomic fundamentals such as inflation and exchange rate stabilization coupled with robust development of human capital.